THE CONVERSATIONAL IMPLICATURE USED BY THE MAIN CHARACTER IN I CARE A LOT MOVIE : A PRAGMATIC ANALYSIS - Fitriant, Nur Azizah; Mahmud, Murni (ELITERATE : Journal of English Linguistics and Literature Studies, 2022)
The aim of this research is to discover the maxims that the main characters in the film "I Care a Lot" break, as well as the many forms of conversational implicatures that occur in the film. This research focuses on film analysis using Grice's implicature theory and cooperative principle (1975). The information was then evaluated using a qualitative descriptive approach. The goal of this study was to improve readers' understanding of pragmatics, particularly those connected to conversational implicatures. In addition, this study might be used as a source of information for future research. The findings demonstrate that the researchers detected 33 conversational implicature utterances, 21 Generalized Conversational Implicature utterances, and 12 Particularized Conversational Implicature utterances among the 225 utterances of the main character in the film "I care a lot." The researchers discovered 34 statements that violated the maxims based on the sorts of maxims proposed by Grice (1975). As a result, the main character frequently violates the rule by using Generalized Conversational implicature.